The influence of marketing strategies in building brand equity at Semen Bosowa Company - Nuzul Qadri; Muh Yunus Amar; Wahda Wahda (Enrichment : Journal of Management, 2023)
The purpose of this study was to examine the effect of marketing strategies in building brand equity in Bosowa cement companies. This research has important contributions in optimizing marketing strategies to build strong brand equity in Bosowa cement company. The contributions include increased competitive advantage, better business growth and additional value creation. In addition, this research also has urgency due to the competitive cement industry and the importance of brand equity in influencing consumer decisions. Because Semen Bosowa is still less competitive with other companies. The population in this discussion are entrepreneurs, contractors, and consumers or direct users of Bosowa Indonesia cement, and in this study researchers used 100 respondents. This research uses sem analysis techniques with smart pls tools. From the tests carried out, it was found that marketing strategies, in this case brand awareness and brand image, have a positive and significant influence on brand equity either directly or mediated by brand loyalty variables, so it can be concluded that marketing strategies have an important role in building brand equity in Bosowa cement companies.